Population development, damage assessment, and susceptibility of maize hybrids to root-lesion nematodes (Pratylenchus neglectus and P. crenatus) under glasshouse conditions - Thiruchchelvan, N.; Kularathna, M.; Moukarzel, R.; Casonato, S.; Condron, L. (Springer Nature, 2025)
Root-lesion nematodes, particularly Pratylenchus neglectus and P. crenatus (PNC), are widely distributed in New Zealand and cause significant damage to maize roots, reducing crop productivity. Despite their economic importance, no comprehensive assessment of commercial maize hybrids’ resistance to PNC has been conducted in the country. Significant variation was observed in the nematode reproduction factor (Rf) and final population (Pf) among hybrids. In Experiment 1 (initial population (Pi) = 1250 PNC kg⁻¹ soil), Rf ranged from 3.1 in hybrid P8500 to 7.1 in hybrid P9127, with Pf values ranging from 3863 to 8903 PNC kg⁻¹ soil + roots in 45 days. In Experiment 2 (Pi = 750 PNC kg⁻¹ soil), Rf ranged from 18.4 in hybrid P1613 to 37.5 in hybrid P8805, with Pf values from 13,784 to 28,426 PNC kg⁻¹ soil + roots in 60 days. These results indicate active nematode reproduction and substantial hybrid-dependent variation in host response. Experiment 3 examined the impact of varying initial inoculum densities (500, 1000 and 1500 PNC kg⁻¹ soil), showing a dose-dependent increase in Pf and corresponding root damage. Susceptible hybrid (P9127) exhibited up to 42% root dry weight and 22% shoot dry weight reductions. This study is the first systematic evaluation of PNC resistance in New Zealand maize hybrids. It identifies P9127 and P8805 as highly susceptible, and P0891, P8500, and P1613 as moderately resistant. These findings offer valuable benchmarks for future breeding and support nematode management in New Zealand.
Keywords: Plant-parasitic nematodes; Host resistance; Biotic stress; Biotic stress; Reproduction factor; Resistance screening; Dry matter loss; Pathogenicity assay